Focal Endometrial Adenocarcinoma in Atypical Polypoid Adenomyoma of Low Malignant Potential - Salman, Coskun; Vaizoğlu, Ferdi; Usubütün, Alp; Balcı, Serdar; Beksaç, Mehmet Sinan (Gynecology Obstetrics & Reproductive Medicine, 2009)
Atypical polypoid adenomyoma is a rare and benign polypoid lesion of uterus with proliferation of irregular endometrial glands embedded in a smooth muscle stroma. If the lesion contains glands that are sufficiently complex to satisfy the criteria for adenocarcinoma, it is called as atypical polypoid adenomyoma of low malignant potential. Patients most commonly present with abnormal uterine bleeding and more than 90% of patients are premenopausal. Although the lesion is benign, it may occasionally be found to coexist with or to precede endometrial adenocarcinoma. This necessitates a careful management which involves hysterectomy in perimenopausal or postmenopausal patients and hysteroscopy with multiple biopsies in younger women desiring future fertility. This report describes a perimenopausal woman with atypical polypoid adenomyoma of low malignant potential with focal adenocarcinoma on endometrial biopsy who subsequently underwent hysterectomy in which no residual malignant lesion was found.